1989
DOI: 10.1111/j.1365-2125.1989.tb03587.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons in vitro, ex vivo, and in vivo of the actions of seven structurally diverse inhibitors of angiotensin converting enzyme (ACE).

Abstract: 1. Seven drugs (captopril, zofenopril, enalapril, ramipril, lisinopril, fosinopril, and SQ 29,852) were compared in vitro in homogenates of aorta, brain, heart, lung, and kidney and in sera of spontaneously hypertensive rats (SHR) both with respect to potencies of their active moieties as inhibitors of angiotensin‐converting enzyme (ACE), and, where applicable, rates of hydrolysis of their prodrug ester functions. 2. In ex vivo dose‐response and time‐course studies, the inhibitory effects of the seven drugs on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(40 citation statements)
references
References 52 publications
0
38
0
1
Order By: Relevance
“…filtration and tubular secretion (Kubo and Cody, 1985;Cushman et al, 1989). Since the conjugate displayed less plasma ACE inhibition but a similar or higher renal ACE inhibition than free captopril, the RSI of the conjugate was increased at all time points (significant from t ϭ 15 min).…”
Section: Discussionmentioning
confidence: 88%
“…filtration and tubular secretion (Kubo and Cody, 1985;Cushman et al, 1989). Since the conjugate displayed less plasma ACE inhibition but a similar or higher renal ACE inhibition than free captopril, the RSI of the conjugate was increased at all time points (significant from t ϭ 15 min).…”
Section: Discussionmentioning
confidence: 88%
“…27 - 28 However, it has been recently shown that brain ACE was not consistently decreased by most of the ACE inhibitors. 29 In addition, antirenin immunization also tended to increase the baroreceptor reflex sensitivity. Therefore, the differences observed between SHR-I and SHR-P could be due to the lower SBP of SHR-P, which allows in the measurement of the baroreceptor reflex sensitivity a greater proportion of the linear steep part of the relation between SBP and heart period to be studied.…”
Section: Figure 4 Bar Graphs Showing the Free Urinary Catecholaminesmentioning
confidence: 99%
“…The two ACE inhibitors were selected because ramipril (1 mg/kg) is lipophilic and is thought to cross the blood-brain barrier, whereas lisinopril (10 mg/kg) is hydrophilic and is less likely to do so. The doses were selected as Cushman et al (1989) showed that they were normalized equivalent oral doses, and they have also been shown to induce renin-angiotensin system manipulation in the brain (Cushman et al, 1989;Lu et al, 2005;Sakaguchi et al, 1988). Separate cohorts received either 7 (short-term) or 42 days (long-term) of treatment until and including the day of surgery.…”
Section: Drug Administrationmentioning
confidence: 99%